2013
DOI: 10.3389/fncom.2013.00185
|View full text |Cite
|
Sign up to set email alerts
|

Model selection for the extraction of movement primitives

Abstract: A wide range of blind source separation methods have been used in motor control research for the extraction of movement primitives from EMG and kinematic data. Popular examples are principal component analysis (PCA), independent component analysis (ICA), anechoic demixing, and the time-varying synergy model (d'Avella and Tresch, 2002). However, choosing the parameters of these models, or indeed choosing the type of model, is often done in a heuristic fashion, driven by result expectations as much as by the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
(82 reference statements)
2
18
0
Order By: Relevance
“…In addition we found that each component contributed significantly to all tested expressions. This small number of necessary primitives is confirmed by psychophysical experiments and by results derived by Bayesian model comparison (Endres, Chiovetto, & Giese, 2013). This finding implies that the efficient dimensionality of the space of dynamic facial expressions, especially for the ones that are frequently used, might be much smaller than what is suggested by the FACS.…”
Section: Introductionsupporting
confidence: 56%
“…In addition we found that each component contributed significantly to all tested expressions. This small number of necessary primitives is confirmed by psychophysical experiments and by results derived by Bayesian model comparison (Endres, Chiovetto, & Giese, 2013). This finding implies that the efficient dimensionality of the space of dynamic facial expressions, especially for the ones that are frequently used, might be much smaller than what is suggested by the FACS.…”
Section: Introductionsupporting
confidence: 56%
“…In an earlier paper [6], we argued that kinematic MPs could be grouped into temporal [7,8,9], spatial [10,11], and spatio-temporal primitives [2]. Temporal MPs are the ones which we use in this paper.…”
Section: Movement Primitivesmentioning
confidence: 98%
“…The smoothness provided by GPs facilitates interpolation to step parameter values to which the MP model has not been exposed to during training. Furthermore, we have shown previously [6] that such GP-MPs are good models for biological gait data, so we hypothesized that they might be suitable for humanoid robots, too. The graphical model of our approach is shown in Figure 5, using plate notation: we would like to generate K movements, each with possibly different parameters l k , e.g.…”
Section: The Morphable Movement Primitive Modelmentioning
confidence: 98%
“…Furthermore, the perception of emotion based on spatio-temporal MPs has been investigated by Roether et al (2009) andChiovetto et al (2018). In our study, we are interested in comparing different MP types in a unified Bayesian framework (Endres et al 2013) with respect to the perception of naturalness.…”
Section: Related Workmentioning
confidence: 99%
“…MPs refer to building blocks of complex movements, but there is little consensus on an exact definition. Consequently, many different types of MPs have been proposed in literature (Endres et al 2013). These types can be classified as spatial (Giszter et al 1992;Tresch et al 1999), temporal (Clever et al 2016;Endres et al 2013), spatio-temporal (d'Avella et al 2003dynamical MPs (Ijspeert et al 2013).…”
Section: Movement Primitivesmentioning
confidence: 99%